Reading the Gospel of Matthew within the global context: A response - Wainwright, Elaine Mary (HTS teologiese studies, 2009)
This article responds to the diversity of approaches in the five papers presented at the Matthew Section of the Society of Biblical Literature, held in Boston (Massachusetts), 21–25 November 2008. This response focuses on an overarching question: what does it mean to read Matthew in a global context? It considers two key areas. The first is location and voice/language and the second, the hermeneutics and methodologies employed and how these enabled John Y.H. Yieh (Virginia Theological Seminary), Andries van Aarde (University of Pretoria), Dorothy Jean Weaver (Eastern Mennonite Seminary), Laura Anderson (Graduate Theological Union, Berkeley) and Lidija Novakovic (Baylor University, Waco) to read Matthew within a global context.